Do as they did: Peer effects explain adoption of conservation agriculture in Malawi - Bell, Andrew R.; Zavaleta Cheek, Jennifer; Mataya, Frazer; Ward, Patrick S. (MDPI, 2018)
Adoption of the trinity of practices known commonly today as conservation agriculture (CA)—maintaining soil cover, reducing tillage, and enhancing soil nitrogen through legumes—is a critical process to the management of erosion in rural landscapes, and maintenance of aquatic habitats and hydropower potential. However, the large literature on the benefits and risks of CA fails to find any universal determinants of adoption, with competing uses for crop residues, availability of labor, and access to physical inputs common constraints appearing in different contexts. We conduct a study in the specific context of Malawi, using ethnographic interviewing to draw out possible decision criteria and machine learning to identify their explanatory power. This study is structured to inform the question: “How do farmers decide to adopt the specific activities of CA in Malawi?” We find that more than any other factor, adoption by neighbors (i.e., peer effects) matters, with possible implications for the overall cost of encouraging CA (e.g., through subsidies) as it is taken up across a landscape.